2017
DOI: 10.1097/dcc.0000000000000233
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Learning in a Cardiac Intensive Care Unit

Abstract: Introduction: Providing high-quality care to every patient is challenging, particularly in critical care units (CCUs). However, this standard can be achieved through organizational learning. Unfortunately, the process of organizational learning in CCUs is not well understood. Objective: The objective of this study is to describe the developmental progression of a cardiac intensive care unit (CICU) to reach its current state of reliably excellent clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 8 publications
0
45
0
Order By: Relevance
“…Psychologically safe learning environments promote learning (Lyman et al, 2017) and contribute to patient safety (Dieckmann & Krage, 2013;Salas, Wilson, Burke, & Priest, 2005). Based on this concept analysis, there is direction on how to create a psychologically safe learning environment for simulation in the health professions and literature to support the need to do so.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychologically safe learning environments promote learning (Lyman et al, 2017) and contribute to patient safety (Dieckmann & Krage, 2013;Salas, Wilson, Burke, & Priest, 2005). Based on this concept analysis, there is direction on how to create a psychologically safe learning environment for simulation in the health professions and literature to support the need to do so.…”
Section: Discussionmentioning
confidence: 99%
“…Fowler and Rigby (1994) argued that students experienced distrust and anxiety during experiential learning activities as they perceived the facilitators as lacking in skills and expertise to provide for the psychological safety of participants. Psychological safety in the health care environment is linked to participants engaging in self-correcting behaviors, as they do not believe they will be punished for mistakes (Aranzamendez, James, & Toms, 2015;Lyman, Ethington, King, Jacobs, & Lundeen, 2017;Tucker & Edmondson, 2003). In studies that addressed psychological safety in simulation, researchers found that increased stress impairs knowledge recall and decreases clinical performance during simulation (Harvey, Bandiera, Nathens, & LeBlanc, 2012), whereas psychological safety is associated with a decrease in anxiety in stressful situations (Ignacio et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Organisational learning (Senge, Ross, Smith, Roberts, & Kleiner, 1994; Singer & Vogus, 2013) is a promising approach for improving health care systems and patient outcomes (Fan et al., 2016; Filice et al., 2013; Lyman, Ethington, King, Jacobs, & Lundeen, 2017; Lyman, Shaw, & Moore, 2017; Nembhard, Alexander, Hoff, & Ramanujam, 2009; Rangachari et al., 2014). The concept of organisational learning arose from a confluence of work in the fields of psychology, systems thinking and organisational behaviour (Rebelo & Gomes, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Organizational learning is linked to better patient outcomes, improved job satisfaction, reduced costs and other benefits (Fan et al, 2016;Lees et al, 2016;Lyman, Ethington, King, Jacobs, & Lundeen, 2017;Lyman, Shaw, & King, 2017;Rangachari et al, 2014;Sadeghifar et al, 2014;Syed & Samreen, 2015). However, the lack of a middlerange theory of organizational learning in hospitals leaves researchers and clinical leaders with little guidance for advancing research and practice in this field.…”
Section: Introductionmentioning
confidence: 99%